1999
DOI: 10.1128/jb.181.2.552-555.1999
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori : a Eubacterium Lacking the Stringent Response

Abstract: Accumulation of 16S rRNA and production of guanosine polyphosphates (pppGpp and ppGpp) were studied during amino acid starvation in three wild-type strains of Helicobacter pylori. All strains exhibit a relaxed phenotype with respect to accumulation of 16S rRNA. This constitutes the first example of a wild-type eubacterium showing a relaxed phenotype. The guanosine polyphosphate levels do not rise as a result of amino acid starvation, as expected for relaxed organisms. However, in both growing and starved cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…The stringent response has been most thoroughly studied in a few copiotrophic species including E. coli (Potrykus and Cashel, 2008), B. subtilis (Ochi et al, 1982) and Legionella pneumophila (Wells and Gaynor, 2006;Zhou et al, 2008;Dalebroux et al, 2009;Edwards et al, 2009). However, there is evidence that species living in different ecological niches have stringent response systems that are structured and regulated differently (Chiaverotti et al, 1981;Belitsky and Kari, 1982;Acosta and Lueking, 1987;Howorth and England, 1999;Scoarughi et al, 1999;Wells and Gaynor, 2006;Zhou et al, 2008). In this work we illuminate several regulatory features of the stringent response in the model oligotroph C. crescentus.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The stringent response has been most thoroughly studied in a few copiotrophic species including E. coli (Potrykus and Cashel, 2008), B. subtilis (Ochi et al, 1982) and Legionella pneumophila (Wells and Gaynor, 2006;Zhou et al, 2008;Dalebroux et al, 2009;Edwards et al, 2009). However, there is evidence that species living in different ecological niches have stringent response systems that are structured and regulated differently (Chiaverotti et al, 1981;Belitsky and Kari, 1982;Acosta and Lueking, 1987;Howorth and England, 1999;Scoarughi et al, 1999;Wells and Gaynor, 2006;Zhou et al, 2008). In this work we illuminate several regulatory features of the stringent response in the model oligotroph C. crescentus.…”
Section: Discussionmentioning
confidence: 94%
“…There are reports of 'relaxed' species, including Helicobacter pylori and Caulobacter crescentus, which neither reduce rRNA transcription nor synthesize ppGpp in a few tested conditions of amino acid starvation (Chiaverotti et al, 1981;Scoarughi et al, 1999). Yet these species still synthesize ppGpp: C. crescentus in glucose (Lesley and Shapiro, 2008) and ammonium (Chiaverotti et al, 1981) starvation, and H. pylori in carbon and serum starvation and acid stress (Wells and Gaynor, 2006;Zhou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The stringent response and (p)ppGpp production have not previously been described for C. jejuni . In fact, apart from one study, which concluded that H. pylori lacked the stringent response (Scoarughi et al ., 1999), this phenomenon has not been described for any of the epsilon‐proteobacteria. Nutrient deprivation has been shown to induce (p)ppGpp accumulation in E. coli and other bacteria (Cashel et al ., 1996; Hammer and Swanson, 1999; Wells and Long, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the numerous stresses encountered by C. jejuni and other related bacteria, it seems surprising that stringent control has never been demonstrated for any of the epsilon proteobacteria, including all Campylobacter , Helicobacter , Wolinella , Arcobacter , Flexispira and Sulfospirillum species. In fact, it was previously reported that H. pylori , with which C. jejuni shares many genetic and phenotypic traits, lacks a stringent response (Scoarughi et al ., 1999). However, both sequenced strains of H. pylori contain a relA / spoT homologue (Tomb et al ., 1997; Alm et al ., 1999), and in the aforementioned study, ppGpp production was not assayed under total nutrient starvation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…sRNA synthesis has been found to be under SC in all bacteria examined to date, with the notable exception of Helicobacter pylori [15]. Conversely, ¢ve of the six archaeal species examined for SC have been shown to present a relaxed phenotype, while to date only one Archaeon, Haloferax volcanii, exhibits SC over sRNA synthesis.…”
Section: Introductionmentioning
confidence: 99%